FRUIT CRACKING AND YIELD OF POMEGRANATE AS AFFECTED BY BORAX WITH IRRIGATION AT DIFFERENT INTERVALS - AHMED, B. (Annals of Agricultural Research, 2014)
An experiment was undertaken to see the response of borax with different irrigation intervals on fruit cracking and yield of pomegranate.Soil application of 0.75% borax at the time of fruit setting, and irrigation at nine days interval decreased the fruit cracking and improved the yield in pomegranate.